Measuring Teacher Students’ Psychological Readiness for Professional Life - Andrey Samoderzhenkov; Elena Kardanova; Akmaral Satova; Ekaterina Orel; Alena Kulikova; Gulmira Mombiyeva; Gulnur Kazakhbaeva; Ainur Duisenbayeva (Вопросы образования, 2021)
In this paper, psychological readiness of teacher students for professional life is understood as a set of personal characteristics such as personality traits, motivation, attitudes and values that contribute to successful teaching. This operational definition does not include teacher’s subject knowledge or teaching skills. The study explores a number of unique evaluation methods to diagnose components of students’ psychological readiness for teaching. The selected methods were localized for Russia and Kazakhstan and tested on national samples from both countries. Psychometric characteristics of these methods were analyzed using classical test theory and item response theory (IRT). A procedure was developed for calculating an integrated index reflecting student’s psychological readiness for starting a teaching career.